The Development of the Survey of Technology Use, Teaching, and Technology-Related Learning Experiences among Pre-Service English Language Teachers in Indonesia - Dyah Setyowati Ciptaningrum (Universitas Muhammadiyah Yogyakarta, 2017)
This study aims to design a survey instrument that can be used to collect information on the relationships between the ICT-related learning experiences of the English language pre-service teachers in Yogyakarta, Indonesia, and their technological pedagogical content knowledge (TPACK).Qualitative and quantitative research methods were used to analyse the degree of the reliability and validity of the instrument. The result suggests that this instrument meets the general requirements to be used in a larger scale of work in investigating the role of pre-service teachers’experiences in learning to use ICT in their pedagogical practice in influencing the development oftheir TPACK.